Pencak Silat Match Score Assist Application - Susanto, Budi (Ann Publisher, 2023)
In 1973 for the first time, pencak silat competed precisely at PON VIII in Jakarta. Until now, matches have always been held at the district level and even ASEAN in the annual activity agenda. In a match, of course, there is an assessment to find the final result of a match, the match assessment tool in each match event is still manual, which uses paper and pen media to determine the value of the match, but such a scoring model has problems in the time of accumulation of total assessments, the loss of assessment data paper after the match and the high costs incurred to buy match assessment tools. It is hoped that the Pencak Silat Match Assist Score Application can help assess pencak silat matches and enjoy its usefulness in all pencak silat martial arts games at the regional, district, and even national levels.